Implications of Bank Regulation for Credit Intermediation and Bank Stability: A Dynamic Perspective - Monika Bucher; Diemo Dietrich; Achim Hauck (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Business cycles imply liquidity risks for banks. This paper explores how these risks influence bank lending over the cycle. With forward-looking banks, lending cycles, credit booms and busts, or suppressed and highly fragile bank systems can emerge, depending on the magnitude of liquidity risks. In this context, regulatory stability-enhancing measures have some unpleasant effects on bank lending. Imposing countercyclical capital adequacy ratio may amplify procyclicality or result in disintermediation, when liquidity risks are only moderate and financial stability is barely a threat. Adopting a regulatory margin call eliminates failures but stops lending for larger liquidity risks whereas a liquidity ratio might be a way to reduce risk-taking without fully hampering credit intermediation.
Keywords: G28; G21; E32; 330